2021
DOI: 10.3390/su13041711
|View full text |Cite
|
Sign up to set email alerts
|

ICT Skills of University Students from the Faculty of Sport and Physical Education during the COVID-19 Pandemic

Abstract: Background: (1) The COVID-19 pandemic has generated significant changes in teaching methods around the world, and the ideal of online education has become a reality. (2) Methods: A questionnaire was modified for this study in order to determine the following levels of Information and Communication Technologies (ICT) skills: file creation, file management, the use of emails, the use of the internet, and online communication. In total, 360 students from the Faculty of Sports and Physical Education (FSPE), Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 28 publications
1
22
0
1
Order By: Relevance
“…The chemistry students also agreed that they need time to up-date and develop their knowledge and skills. A similar finding was made by Batez [13] who observed that students need to update their ICT knowledge and skills to meet with the demand of virtual education in the covid-19 era.…”
Section: Discussionsupporting
confidence: 77%
“…The chemistry students also agreed that they need time to up-date and develop their knowledge and skills. A similar finding was made by Batez [13] who observed that students need to update their ICT knowledge and skills to meet with the demand of virtual education in the covid-19 era.…”
Section: Discussionsupporting
confidence: 77%
“…Educational activities also conform to health protocols, namely maintaining distance, preventing crowds, and reducing physical activity. At present, learning and student activities generally use online media, research activities have decreased in volume, and campus management activities are directed to the online assignment (Batez, 2021;Cameron-Standerford et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Spanish researchers have highlighted how the use of ICTs has negatively impacted teachers' health and how the students considered that the university teachers were capable and could change from face-to-face to online education [65,66]. Although few studies and reports have focused on the university level [28,67,68], the implementation of online teaching was carried out in some scenarios without training, resources, or skills, implying longer hours of working [69].…”
Section: Education Icts and Covid-19mentioning
confidence: 99%
“…In Ecuador, recent researches have focused on the mental health of Ecuadorian students focusing on the pressure and impact of using ICTs [72], resources available at the time [60], and the experience of the teacher [72]. In Spain publications, researchers have focused on students' perspectives regarding the change to the education, use of the ICTs, and only little has included the teachers' point of view [28,65,67,72,74]. One Spanish research had as participants the university teachers training the future teachers from elementary schools, although the objective was to evaluate the impact of ICTs on the teaching process [75].…”
Section: Education Icts and Covid-19mentioning
confidence: 99%
See 1 more Smart Citation